Automatic Generation Control and Automatic Voltage Regulator Design for Load Frequency Control of Interconnected Thermal Power System (Global Journals of Research in Engineering, 2022)
This paper presents a new model for each component of Automatic generation control (AGC) and automatic voltage regulator (AVR) loops considering generator rate constraints (GRC) of one and two areas interconnected thermal power system. Any mismatch between system generation and demand results in a change in system frequency that is highly undesired. Excitation of the generator must be regulated in order to match the power demand, otherwise, the bus voltage may fall beyond the permitted limit. In this paper, a simulation model is developed for each component of AGC and AVR loops considering generator rate constraints. Although the frequency variation was found to be less with suitable controllers when the GRC is not considered, it is not the frequency variation. The frequency variation can be found when GRC is considered and then accordingly the controller is tuned. So that the required frequency and power interchange with adjacent structures are maintained in order to minimize the transient deviations and to provide zero steady-state error in a proper short time, the response without GRC is compared with the analysis done with the GRC, the behaviour of the planned is checked by MATLAB SIMULINK software.
Keywords: automatic generation control (AGC); automatic voltage regulator (AVR); automatic load frequency control (ALFC); generation rate constraint (GRC)